2011
DOI: 10.1557/jmr.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring substrate-independent modulus of thin films

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 14 publications
1
133
0
Order By: Relevance
“…Unfortunately, the form of this function differs according to the authors who employed it. Mencik et al [48], Hay and Crawford [53] and Sawa et al [49] confirmed the general form of Eq. (9) even if the parameter ξ has been associated to different expressions.…”
Section: Indentation On Thin Filmsmentioning
confidence: 82%
See 1 more Smart Citation
“…Unfortunately, the form of this function differs according to the authors who employed it. Mencik et al [48], Hay and Crawford [53] and Sawa et al [49] confirmed the general form of Eq. (9) even if the parameter ξ has been associated to different expressions.…”
Section: Indentation On Thin Filmsmentioning
confidence: 82%
“…Gao's function has already been applied by numerous authors [48][49][50][51][52][53]. Unfortunately, the form of this function differs according to the authors who employed it.…”
Section: Indentation On Thin Filmsmentioning
confidence: 99%
“…At least eight CSM-mode indentations were performed on each sample, and the hardness H and modulus E were calculated using the Oliver-Pharr method [35] by averaging over the depth range of 1000-1800 nm. The substrate effect on E was then corrected using the Hay method [36]. Because the 2 lm depth is less than 20% of NCC film thicknesses (>10 lm), the substrate effect on H is generally insignificant [37].…”
Section: Methodsmentioning
confidence: 99%
“…Finite element analysis suggests that indents into coatings on the more compliant silica substrates will have an additional substrate effect that would artificially reduce the extracted coating modulus by as much as 5% [29]. Comparing the moduli measured on silica to those measured on …”
Section: A Nanoindentationmentioning
confidence: 99%